2021
DOI: 10.1186/s12872-021-02406-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between IL-6 levels and the angiographic severity of coronary artery disease following percutaneous coronary intervention in acute coronary syndrome patients

Abstract: Background The present investigation was developed for the exploration of the association between IL-6 levels and acute coronary syndrome (ACS) findings upon angiographic evaluation. Methods A retrospective review of 346 patients suffering from chest discomfort that underwent coronary angiography was performed. The SYNergy between Percutaneous Coronary Intervention with TAXus and cardiac surgery (SYNTAX) score (SS) and SS II were used to gauge ACS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…A systematic review and meta-analysis of studies investigated the association of CRP, IL-6 and fibrinogen with the risk of recurrent stroke, and these three factors were found to be closely linked to the extent of coronary artery disease in ACS patients. Recently, higher circulating IL-6 levels in community-dwelling individuals have been shown to be linearly associated with a higher long-term risk of incident ischemic stroke, and independent of conventional vascular risk factors, they have been reported in several other studies (9,45,46). These reports and our results demonstrate that IL-6 is an atherothrombosis-associated inflammatory response cytokine.…”
Section: Discussionsupporting
confidence: 86%
“…A systematic review and meta-analysis of studies investigated the association of CRP, IL-6 and fibrinogen with the risk of recurrent stroke, and these three factors were found to be closely linked to the extent of coronary artery disease in ACS patients. Recently, higher circulating IL-6 levels in community-dwelling individuals have been shown to be linearly associated with a higher long-term risk of incident ischemic stroke, and independent of conventional vascular risk factors, they have been reported in several other studies (9,45,46). These reports and our results demonstrate that IL-6 is an atherothrombosis-associated inflammatory response cytokine.…”
Section: Discussionsupporting
confidence: 86%
“…Tanindi et al [14] had found that IL-6 was associated with more extensive and severe CAD as represented by GS. Despite signi cant association between high levels of IL-6 in single-and multi vessel disease groups as compared with controls, Mokhtar ER et al [15] ndings did not show signi cant association between IL-6 and GS. Gotsman I et al [16] reported that there was signi cant correlations between interleukin-6 with the severity of CAD assessed by the number of obstructed coronary vessels and the lesions severity.…”
Section: Discussionmentioning
confidence: 82%
“…Tanindi et al [ 13 ] had found that IL-6 was associated with more extensive and severe CAD as represented by GS. Despite significant association between high levels of IL-6 in single- and multi vessel disease groups as compared with controls, Mokhtar ER et al [ 14 ] findings did not show significant association between IL-6 and GS. Gotsman I et al [ 15 ] reported that there was significant correlations between interleukin-6 with the severity of CAD assessed by the number of obstructed coronary vessels and the lesions severity.…”
Section: Discussionmentioning
confidence: 93%